Seasonality, weather and climate affect home range size in roe deer across a wide latitudinal gradient within Europe. (15th July 2013) - Morellet, Nicolas; Bonenfant, Christophe; Börger, Luca; Ossi, Federico; Cagnacci, Francesca; Heurich, Marco; Kjellander, Petter; Linnell, John D. C.; Nicoloso, Sandro; Sustr, Pavel; Urbano, Ferdinando; Mysterud, Atle
Summary: Because many large mammal species have wide geographical ranges, spatially distant populations may be confronted with different sets of environmental conditions. Investigating how home range (HR) size varies across environmental gradients should yield a better understanding of the factors affecting large mammal ecology. We evaluated how HR size of a large herbivore, the roe deer ( Capreolus capreolus ), varies in relation to seasonality, latitude (climate), weather, plant productivity and landscape features across its geographical range in Western Europe. As roe deer are income breeders, expected to adjust HR size continuously to temporal variation in food resources and energetic requirements, our baseline prediction was for HR size to decrease with proxies of resource availability. We used GPS locations of roe deer collected from seven study sites (EURODEER collaborative project) to estimate fixed‐kernel HR size at weekly and monthly temporal scales. We performed an unusually comprehensive analysis of variation in HR size among and within populations over time across the geographical range of a single species using generalized additive mixed models and linear mixed models, respectively. Among populations, HR size decreased with increasing values for proxies of forage abundance, but increased with increases in seasonality, stochastic variation of temperature, latitude and snow cover. Within populations, roe deer HR size varied over time in relation to seasonality and proxies of forage abundance in a consistent way across the seven populations. Thus, our findings were broadly consistent across the distributional range of this species, demonstrating a strong and ubiquitous link between the amplitude and timing of environmental seasonality and HR size at the continental scale. Overall, the variability in average HR size of roe deer across Europe reflects the interaction among local weather, climate and seasonality, providing valuable insight into the limiting factors affecting this large herbivore under contrasting conditions. The complexity of the relationships suggests that predicting ranging behaviour of large herbivores in relation to current and future climate change will require detailed knowledge not only about predicted increases in temperature, but also how this interacts with factors such as day length and climate predictability. Abstract : This paper presents the first pan‐European study of the biogeography of home range size in a large herbivore based on GPS locations in seven study sites across Europe. The findings are broadly consistent across the distributional range of this species, demonstrating a strong and ubiquitous link between the amplitude and timing of environmental seasonality and home range size at the continental scale.